THE IMPORTANCE OF DIDACTIC GAMES IN THE DEVELOPMENT OF SPEECH ACTIVITY OF PUPILS - Boychayeva Sharifa Saidkulovna (Web of Journals Publishing, 2024)
This article reflects on the use of didactic games in increasing the level of knowledge of elementary pupils and in the development of speech activity, the main types of games, and the fact that pupils act with interest during the game.
Keywords: Didactics, speech cultivation, ability, method, children, play, education, computer, thinking, creative ability.